1994
DOI: 10.4141/cjas94-010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mobile, open-circuit indirect calorimetry system

Abstract: 65-71. A system for the rapid determination of 02 consumption, CO2 production and subsequent indirect estimation of energy metabolism of ruminants has been updated and validated. The accurate determination of gas temperature, relative humidity, absolute pressure and flow is important to the overall use of the system. Analogue outputs from the specific analyzers were multiplexed and then routed to a data acquisition system with appropriate software control.Subsequent data processing included modification to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 7 publications
0
24
0
2
Order By: Relevance
“…As a modified version of the respiration chamber, Kelly et al (1994) describe development of a portable, open-circuit indirect calorimetry system, which can be used to measure CH 4 emissions from sheep and cattle. The system is based on O 2 , CO 2 and CH 4 analysers mounted on a cart for ease of mobility.…”
Section: Portable Analysermentioning
confidence: 99%
“…As a modified version of the respiration chamber, Kelly et al (1994) describe development of a portable, open-circuit indirect calorimetry system, which can be used to measure CH 4 emissions from sheep and cattle. The system is based on O 2 , CO 2 and CH 4 analysers mounted on a cart for ease of mobility.…”
Section: Portable Analysermentioning
confidence: 99%
“…This demand arises from the need to verify inventories, verify mitigation claims on-farm and measure large numbers of animals to determine the genetic parameters of methane output (Chagunda et al, 2009;McEwan et al, 2012). Although mobile respiration hood systems exist for on-farm use (Kelly et al, 1994), and RC studies using thousands of animals are now being conducted (Arthur et al, 2012), this is extremely slow and expensive. Robinson et al (2010) identified that short-term measures of methane production were strongly correlated with DMP and can be used to obtain short-term on-farm emission data without need for an RC.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of respiration calorimetry chambers (Kelly et al 1994;Galbraith et al 1998;Murray et al 1999), isotopic techniques (Murray et al 1976;France et al 1993), tracer techniques [sulfur hexafluoride (SF 6 )], Kaharabata et al 2000; and mass balance/micrometeorological techniques (Lassey et al 1997;Sauer et al 1998;Harper et al 1999). The advantages and disadvantages of each method have been reviewed by Johnson and Johnson (1995).…”
Section: Measurement Of Methane Emission From Dairy Cattlementioning
confidence: 99%